Laminin α4 Expression in Human Adipose Tissue Depots and Its Association with Obesity and Obesity Related Traits - Tobias Hagemann; Paul Czechowski; Adhideb Ghosh; Wenfei Sun; Hua Dong; Falko Noé; Christian Wolfrum; Matthias Blüher; Anne Hoffmann (Biomedicines, 2023)
Laminin α4 (LAMA4) is one of the main structural adipocyte basement membrane (BM) components that is upregulated during adipogenesis and related to obesity in mice and humans. We conducted RNA-seq-based gene expression analysis of LAMA4 in abdominal subcutaneous (SC) and visceral (VIS) adipose tissue (AT) depots across three human sub-cohorts of the Leipzig Obesity BioBank (LOBB) to explore the relationship between LAMA4 expression and obesity (N = 1479) in the context of weight loss (N = 65) and metabolic health (N = 42). We found significant associations of LAMA4 with body fat mass (p < 0.001) in VIS AT; higher expression in VIS AT compared to SC AT; and significant relation to metabolic health parameters e.g., body fat in VIS AT, waist (p = 0.009) and interleukin 6 (p = 0.002) in male VIS AT, and hemoglobin A1c (p = 0.008) in male SC AT. AT LAMA4 expression was not significantly different between subjects with or without obesity, metabolically healthy versus unhealthy, and obesity before versus after short-term weight loss. Our results support significant associations between obesity related clinical parameters and elevated LAMA4 expression in humans. Our work offers one of the first references for understanding the meaning of LAMA4 expression specifically in relation to obesity based on large-scale RNA-seq data.